(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the influence of benzocaine and eugenol concentrations as anesthetics on the induction and recovery of juvenile pacu (P. mesopotamicus). 288 juvenile pacu were used in a completely randomized design consisting of 12 concentrations of benzocaine (12.5; 25; 37.5; 50; 62.5; 75; 87.5; 100; 112.5; 125; 137, 5 and 150 mg.L-1) and 11 concentrations of eugenol (7.5; 15; 22.5; 30; 37.5; 45; 52.5; 60; 67.5; 75 and 82.5 mg. L-1) and a control group. The fish were divided into 24 lots, with 12 fish chosen at random and individually exposed to each anesthetic concentration in a glass aquarium with a useful volume of 30L, but containing only 10L of water. Benzocaine proved to be efficient for anesthesia in juvenile pacu at different concentrations, except for values ​​12.5 and 25 mg.L-1. Eugenol was effective for anesthesia, except for the values ​​7.5 and 15 mg.L-1. The best dose of benzocaine and eugenol for sedation and recovery is 75 mg.L-1 and 52.5 mg.L-1, respectively.